2019
DOI: 10.1177/1071100718822839
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Medial Cuneiform Position Correlation With Patient-Reported Outcomes Following Cotton Osteotomy for Reconstruction of the Stage II Adult-Acquired Flatfoot Deformity

Abstract: Background: Residual supination of the midfoot during reconstruction of the stage II adult-acquired flatfoot deformity (AAFD) is often addressed with a medial cuneiform (Cotton) osteotomy after adequate correction of the hindfoot valgus deformity. The purpose of this study was to determine if there was a correlation between postoperative alignment of the medial cuneiform and patient-reported outcomes. Methods: Sixty-three feet in 61 patients with stage II AAFD who underwent a Cotton osteotomy as part of a flat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 16 publications
(56 reference statements)
0
24
1
Order By: Relevance
“…Small differences in angles may have significant consequences on patient-reported outcomes in foot and ankle surgery. 6,7 In our study, the difference in the mean IMA between normal and control patients was only 6.7 degrees, but most surgeons would agree that correction of the IMA is an essential part of an HV operation. 1,8…”
Section: Discussioncontrasting
confidence: 47%
“…Small differences in angles may have significant consequences on patient-reported outcomes in foot and ankle surgery. 6,7 In our study, the difference in the mean IMA between normal and control patients was only 6.7 degrees, but most surgeons would agree that correction of the IMA is an essential part of an HV operation. 1,8…”
Section: Discussioncontrasting
confidence: 47%
“…8 Although the authors of this study noted an average graft size of 5.5 mm (range 4-10, SD 0.9) in their cohort of 63 feet, they also concluded that graft size alone did not correlate with changes in patient-reported outcomes, but rather the final postoperative position of the medial cuneiform. 8 Although some studies have shown that instability of the first ray at the tarsometatarsal joint should be indicated for arthrodesis, there is no definitive contraindication for performing a Cotton osteotomy. 25 Cotton osteotomy is a technically easy operative option that has the advantage of preserving motion at the medial column.…”
Section: Rationalementioning
confidence: 60%
“…8 Although the authors of this study noted an average graft size of 5.5 mm (range 4-10, SD 0.9) in their cohort of 63 feet, they also concluded that graft size alone did not correlate with changes in patient-reported outcomes, but rather the final postoperative position of the medial cuneiform. 8…”
Section: Rationalementioning
confidence: 60%
“…It is also very important to mention that some of the 3D AAFD components demonstrated in this study to be appropriately assessed by the FAO (individually assessed FAA, TCA, HMA, and SHA) have been shown to significantly influence surgical correction and clinical outcomes of AAFD patients treated surgically, including the correction of the forefoot supination and longitudinal arch collapse deformity by a first tarsometatarsal fusion or a Cotton osteotomy (measured by the FAA) 14,25 ; correction of forefoot abduction by a lateral column lengthening procedure (measured by the TCA) 9,12 ; and improvement of the valgus deformity of the hindfoot by a medializing calcaneal osteotomy (assessed by both SHA and HMA). 10,13 Bearing that in mind, improvements in the FAO could potentially represent a more complete multiplanar assessment of deformity correction, possibly correlated with improved outcomes.…”
Section: Discussionmentioning
confidence: 96%